Digital Financial Literacy and Financial Well-Being: Unpacking the Roles of Financial Behavior and Financial Stress - Sri Fitri Wahyuni; Dahrani Dahrani; Maya Sari; Izmi Adinda Putri; Alfina Nabila (International Journal of Business Economics (IJBE), 2025)
Purpose—This study aims to analyze the effect of Digital Financial Literacy on Financial Behavior, Financial Stress, and Financial Well-being among students of Islamic universities in Medan. This study also examines the mediating role of Financial Behavior and Financial Stress in the relationship between Digital Financial Literacy and Financial Well-being.Methodology— The target population of this study consisted of students who had previously taken financial management courses. The sampling technique used was accidental sampling, in which respondents were selected based on their availability and willingness to participate at the time of data collection. This study employed a non-probability sampling method, using an online questionnaire distributed through Google Forms to collect data from 385 students at private universities in Medan. The collected data were then analyzed using the SmartPLS program with the SEM-PLS approach.    Findings – The results showed that Digital Financial Literacy has a significantly positive effect on financial behavior and Financial Well-being. Additionally, it was found that digital financial literacy has a significant negative impact on financial well-being, contributing to financial stress. Financial behavior is shown to have a significant positive effect on financial well-being. In contrast, financial stress negatively impacts financial well-being but also positively influences financial behavior.Originality/Novelty – This research model includes four variables and utilizes the notion of mediation by using SEM-PLS to evaluate each relationship in the model.Implications—This study implies that improving digital financial literacy can significantly promote individual financial well-being directly and indirectly through positive financial behavior and reduced financial stress.